Rank one polynomial modules over the quantum group of type A1. Issue 6 (3rd June 2022) - Xia, Limeng; Feng, Ge; Hu, Naihong
Abstract: In this article, we classify all rank one polynomial modules over the quantum groups U q ( s l 2 ) and U q ( s l 2 ) for generic q . We also provide the equivalent conditions for the simplicity of these modules.